Autonomous aerial robot using dual‐fisheye cameras. Issue 4 (25th February 2020) - Gao, Wenliang; Wang, Kaixuan; Ding, Wenchao; Gao, Fei; Qin, Tong; Shen, Shaojie
Abstract: Safety is undoubtedly the most fundamental requirement for any aerial robotic application. It is essential to equip aerial robots with omnidirectional perception coverage to ensure safe navigation in complex environments. In this paper, we present a light‐weight and low‐cost omnidirectional perception system, which consists of two ultrawide field‐of‐view (FOV) fisheye cameras and a low‐cost inertial measurement unit (IMU). The goal of the system is to achieve spherical omnidirectional sensing coverage with the minimum sensor suite. The two fisheye cameras are mounted rigidly facing upward and downward directions and provide omnidirectional perception coverage: 360° FOV horizontally, 50° FOV vertically for stereo, and whole spherical for monocular. We present a novel optimization‐based dual‐fisheye visual‐inertial state estimator to provide highly accurate state‐estimation. Real‐time omnidirectional three‐dimensional (3D) mapping is combined with stereo‐based depth perception for the horizontal direction and monocular depth perception for upward and downward directions. The omnidirectional perception system is integrated with online trajectory planners to achieve closed‐loop, fully autonomous navigation. All computations are done onboard on a heterogeneous computing suite. Extensive experimental results are presented to validate individual modules as well as the overall system in both indoor and outdoor environments.